Characterization and Synthesis of CdO and 〖CdO〗_(1-x):S_x Films by Pulsed Laser Deposition - A. Thuhaib, Omar; Hashim, Hassan (Al-Nahrain Journal of Science, 2021)
In this work, we analyze the effects of S doping on the structural and optical characteristics of pure cadmium oxide (CdO) films at varying concentrations of : (X = 0.2, 0.4, and 0.6), Sulfur is a chemical element with the atomic number 16 and the symbol S. The films were created using a laser-induced plasma (LIP) with a wavelength of 1064 nm and a duration of 9 ns at a pressure of mbar. X-ray diffraction studies revealed that all of the produced films are polycrystalline. The topography of the film’s surface was evaluated using AFM, and the findings revealed that as the amount of doping increases, so does the grain size, along with an increase in the average roughness. The absorbance spectrum of the wavelength range (350-1100) nm was used to investigate the optical characteristics of all films. This rise might be the so-called Borsstein-Moss displacement has been viewed as a result of this. because the lowest layers of the conduction beams are densely packed with Because electrons require more energy to move, it seems as though the energy disparity widens.